2016
DOI: 10.3897/neobiota.30.8201
|View full text |Cite
|
Sign up to set email alerts
|

Elevational distribution and photosynthetic characteristics of the invasive tree Spathodea campanulata on the island of Tahiti (South Pacific Ocean)

Abstract: Successful invasion is often due to a combination of species characteristics (or invasiveness) and habitat suitability (or invasibility). Our objective was to identify preferred habitats and suitable environmental conditions for the African tulip tree Spathodea campanulata (Bignoniaceae), one of the most invasive alien trees on the tropical island of French Polynesia (South Pacific Ocean), in relation to its distribution and photosynthesis capacity. Spathodea abundance and leaf chlorophyll fluorescence Fo', ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
1
0
3
Order By: Relevance
“…Conforme relato de moradores todas as plantas encontradas de espatódea foram introduzidas propositalmente, com a finalidade de embelezamento da residência, não sendo verificado a sua propagação espontânea como relatado em outras áreas do mundo (Lugo, 2004;Labrada e Diaz-Medina, 2009;Larrue et al 2016).…”
Section: Resultados E Discussõesunclassified
See 1 more Smart Citation
“…Conforme relato de moradores todas as plantas encontradas de espatódea foram introduzidas propositalmente, com a finalidade de embelezamento da residência, não sendo verificado a sua propagação espontânea como relatado em outras áreas do mundo (Lugo, 2004;Labrada e Diaz-Medina, 2009;Larrue et al 2016).…”
Section: Resultados E Discussõesunclassified
“…A espatódea é considerada por diversos autores como árvore invasora de biomas pelo mundo (Lugo, 2004;Labrada e Diaz-Medina, 2009;Larrue et al 2016) devendo a sua substituição por espécies nativas frutíferas ser estimulada.…”
Section: Introductionunclassified
“…Since this temperature is not lethal for the embryo of seed, germination remains possible after LDD. Additionally, Spathodea seedlings and adult trees were observed in natural environments with extreme low temperatures reaching less than 10°C (Larrue et al, 2016). Furthermore, our simulation indicated that most seeds settled on the eastern, humid side of the islands (windward coast), and the high humidity at these sites is a preferred condition for seed germination of Spathodea (Larrue et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Menariknya, masyarakat Afrika secara tradisional menggunakan ekstrak kulit batang dari S. campanulata untuk mengobati luka dan percobaan terhadap tikus di laboratorium menunjukkan hasil yang sama (Ofori-Kwakye et al 2011). Jenis ini patut di waspadai karena pohon dewasa mampu beregenerasi melalui akar dan patahan cabang (PIER 2016), dan permudaannya diketahui toleran terhadap naungan dan mampu beradaptasi pada rentang ketinggian lokasi yang besar (0-1000 mdpl) (Larrue et al 2014(Larrue et al , 2016 sehingga dapat bersaing dengan jenis asli lainnya. Diperlukan penelitian lebih lanjut tentang perkembangan jenis ini di Kalimantan, khususnya ekologi, penyebaran dan potensi invasi di dalam kawasan hutan.…”
Section: Keragaman Dan Penyebaran Jenis Invasif DI Khdtk Sambojaunclassified